Governança europeia e atores subnacionais: A atuação do comitê das regiões na crise migratória (2015-2019) - Brunetta, Pedro Costa (2022)
The migratory crisis in the Mediterranean demanded efforts from European cities to receive and integrate a large number of people in their midst. The event represented a milestone for the new conception of a common migration policy of the European Union (EU). Based on the precepts of multi-level governance, the EU bodies coordinated in 2015 to formulate the European Agenda on Migration, which was implemented in 2018 and developed in 2019. From this year on, new challenges were necessary to contemplate the risks of the pandemic of Covid-19. The work aims to analyze the performance of cities and regions in facing the migratory crisis at the community level. It is argued that the Committee of the Regions (CR) fulfilled the role of representing subnational actors in the negotiations for the European Agenda on Migration. In order to analyze the process, implementation and application of the community migration policy, the documents issued by the CR to the EU's deliberative bodies are considered, as well as the interaction with other subnational actors and civil society agents. The research relies on the theoretical framework of International Relations on migration, multilevel governance and subnational actors to carry out a case study on the migration crisis from 2015 to 2019.